2019
DOI: 10.1111/ecog.04665
|View full text |Cite
|
Sign up to set email alerts
|

Current and projected future risks of freshwater fish invasions in China

Abstract: Biological invasions are a primary threat to global biodiversity, supporting mounting calls for the development of early‐warning systems to manage existing and emerging invaders. Here, we evaluated the geographical pattern of invasion risks of currently established and potentially emerging nonnative freshwater fishes in China by jointly considering the threats of introduction and establishment under climate change. Introduction threats were estimated according to proxies of human activities and propagule press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Studies have shown that species' range size is a good predictor of invasiveness (Ricciardi & Rasmussen, 1998), which has led to the 'niche breadth-invasion success hypothesis', with generalist species with broad niches more likely to successfully invade than specialist species with narrow niches (Vázquez, 2006). Niche analysis also allows us to predict how a specific system could be at risk based on the niche overlap between source and recipient regions for NNS (Liu et al, 2019). This is because the niche of a species changes very slowly through space and time (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that species' range size is a good predictor of invasiveness (Ricciardi & Rasmussen, 1998), which has led to the 'niche breadth-invasion success hypothesis', with generalist species with broad niches more likely to successfully invade than specialist species with narrow niches (Vázquez, 2006). Niche analysis also allows us to predict how a specific system could be at risk based on the niche overlap between source and recipient regions for NNS (Liu et al, 2019). This is because the niche of a species changes very slowly through space and time (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, previously banned species may still be available in stores or on online marketplaces. Preventative measures are deemed the most effective NNS management options (Leung et al, 2002; Ricciardi & MacIsaac, 2022; Roy et al, 2014), but they require the identification of risky traded species with high likelihoods of introduction, establishment and spread (Liu et al, 2019). There is therefore a pressing need for a quantitative method that allows this.…”
Section: Introductionmentioning
confidence: 99%
“…43 Every day, it is likely that enormous numbers of individuals move across biogeographic barriers at a global scale. 44,45 Though only a small fraction of the translocated species survive, 46 the expansion of NAS has greatly altered fish biogeography, especially in freshwater ecosystems, reducing the uniqueness of fish fauna 47 and leading to biotic homogenization by reducing beta diversity. 48,49 China is a vast country with diverse environments which allows NAS to spread far and wide.…”
Section: Introductionmentioning
confidence: 99%
“…Species distribution models, which identify relationships between observed occurrences and environmental predictors by using statistical models, or theoretically derived response curves (Elith & Leathwick, 2009; Srivastava, Lafond & Griess, 2019), have now emerged as a promising early warning tool in alien species management. In addition to quantifying geographical patterns of risks from alien species (Yates et al, 2018; Liu et al, 2019) and helping optimize control strategies (Giljohann et al, 2011), species distribution models are also particularly useful for predicting the suitability of new areas for alien species invasions under future climate scenarios (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%